STRATEGI IMPLEMENTASI BUDAYA SEKOLAH INKLUSI RAMAH ANAK BAGI SISWA SLOW LEARNER: STUDI KASUS DI SDN 1 TAMANREJO BLORA - Khoirul Mahmud; Tri Joko Raharjo; Liftiah Liftiah; Ali Formen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the strategies and implementation of an inclusive child-friendly school culture for slow learner students at SDN 1 Tamanrejo, Blora. Using a qualitative case study approach, data were collected through observation, in-depth interviews with the classroom teacher, and documentation of one fourth-grade student (Khoirul Anwar, pseudonym) who experienced learning difficulties in mathematics and Indonesian language. The results showed that the implemented strategies included clear and concise instructions, breaking material into small parts, use of visual and concrete media (pictures, videos, real objects), additional time for completing assignments, positive reinforcement, and parental involvement in regular study guidance at home. However, challenges remain due to the absence of special assisting teachers (GPK), lack of formal assessment modifications, and limited assistive technology. Khoirul Anwar showed significant improvements after three months: increased self-confidence, improved reading ability, and more active participation in group work. The inclusive culture is still in the early stage, but the teacher's caring professional identity and peer empathy are positive assets. This study recommends ongoing teacher training on differentiated instruction for slow learners, multi-stakeholder collaboration, and modified assessment systems to build a sustainable inclusive school culture.